The Effect of Motivation, Commitment, and Work Discipline on Work Productivity in Grapari Medan Putri Hijau Service Employees - Lilyan Tasaria; Emi Wakhyuni (International Journal of Management, Economic and Accounting, 2024)
The research analysis aims to determine whether motivation, commitment and work discipline affect work productivity. The data analysis technique used is an associative research method with the help of the SPSS version 19 program. This research uses multiple linear regression analysis. The sample in this study was 37 respondents. Primary data collection uses a questionnaire. The research results show that motivation has a partially positive and significant effect on work productivity. Commitment has a partially significant effect on work productivity. Work discipline does not have a positive and partially significant effect on work productivity. Motivation, commitment and work discipline simultaneously have a positive and significant effect on work productivity.